Religion as a Source of Violence: Contending the Narrative of Political Violence Perpetrated in the Name of Islam in Bangladesh - Hassan, Muhammad (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2023)
Since Bangladesh emerged as an independent country, violence has become a part of its political process and activism. This paper challenges a dominant narrative that has been discursively constructed and promoted by secularist communities, civil societies, political parties (including the ruling party), and groups in Bangladesh throughout the years. A dominant narrative about religious violence claims Islamists are primarily responsible for political violence in Bangladesh. However, based on a robust analysis of thirty years of data on violence and other of credible sources, I have found that the dominant narrative is not backed by factual and quantitative evidence or a popular mandate but is constructed primarily to support and legitimize political persecution in the politics of Bangladesh. This paper offers a counter-narrative and argues that in Bangladesh, violence has become a political tool for opposition groups to acquire power and for incumbent regimes to retain power. Moreover, it states that religious parties are less violent than secular groups in Bangladesh.